Successful treatment of three synchronous primary malignant tumours—reflection on surgical, pathological and oncological aspects and decision making. Issue 4 (6th April 2018) - Ágoston, Emese Irma; Somorácz, Áron; Madaras, Lilla; Zaránd, Attila; Szentmártoni, Gyöngyvér; Orosz, Zsuzsanna; Dank, Magdolna; Baranyai, Zsolt
Abstract: We report a case of a patient with triple synchronous primary malignancies (breast, colon, kidney) which has not been previously reported in the literature. A 70-year-old woman was diagnosed with invasive ductal carcinoma of the left breast with axillary lymph node metastasis. During the staging period, renal cell carcinoma on the left kidney and mucinous adenocarcinoma in the proximal colon were found. Since the breast tumour demonstrated favourable biology, aromatase inhibitor therapy had been started and simultaneous right colectomy and left nephrectomy was performed. Six months after the first diagnosis, left sector excision and axillary block dissection were performed. Adjuvant FEC chemotherapy was administered, followed by radiotherapy. During the 16-month follow-up period disease recurrence was not detected.